Poverty Alleviation — A Push Towards Unsustainability in Bangladesh? - Hossain, Md Amzad; Marinova, Dora (Queensland Department of Main Roads, Brisbane, 2005)
Social, economic, educational and infrastructure development programs in Bangladesh, including national and international aid and grants, focus on the agenda of ‘poverty alleviation’. However, they are not performing well as social and environmental degradation is on the increase. The paper analyses the reasons for the failure of development programs from a sustainability point of view. Some explanations are provided through the views of Bangladeshi rural activists, including Baul philosophers. They cover: (1) exclusion of poor people from participation in development programs, especially in natural resource management; and (2) widespread corruption accompanying foreign aid. ’Moderate poverty’ is seen in Bangladeshi culture as acceptable given the country’s conditions. It actually promotes a more sustainable way of living. ‘Poverty’ should be seen as culturally embedded and within the context of population growth and sustainable consumerism. ‘Poverty alleviation’ as promoted in development projects in Bangladesh is neither possible nor desirable, as it is not coupled with the means to achieve sustainability. The paper makes recommendations how to overcome poverty, using local knowledge and developmental wisdom. The outlined approaches relate to sustainability education, self-reliance and pro-sustainable ways of living.